Pengembangan LKPD Kimia Berbasis Science, Environment, Technology, and Society (SETS) Materi Laju Reaksi - Iqbal Pranowo, Muhammad; Linda, Roza; Haryati, Sri (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
This study was designed using a Research and Development design with the ADDIE development model. The ADDIE development model has five stages, namely Analysis, Design, Development, Implementation, and Evaluation. This research was only up to the development stage, the Implementation Stage was not carried out because the research objectives were limited to obtaining a proper / valid LKPD product based on the aspects of content feasibility, SETS characteristics, language, presentation, and graphics through assessment by validators. Data in the form of assessments and suggestions by a team of validators, teacher respondents and students. From the research results, obtained the validation value with a score of 91.19%. The scores for user responses by teachers and students were 90.38% and 90.1%, respectively, with very good criteria. Keywords: Student Activity Sheet, Science, Environment, Technology and Society (SETS), ADDIE, Reaction Rate